(untitled) - Giddens, Anthony (New York, NY, 2005)
Introduction to Sociology, Fifth Edition, organizes the core concepts of modern sociology around the unifying theme of globalization. Taking a comparative approach, the authors examine American society in a global and historical context, underscoring the wide diversity of social forms and social change. The authors emphasize the connections between American and world societies and the integral role of individuals in shaping both local and global society.
Keywords: Sociology,Xã hội học